Design and optimization of a series of 4-(3-azabicyclo[3.1.0]hexan-3-yl)pyrimidin-2-amines: Dual inhibitors of TYK2 and JAK1. Issue 10 (15th May 2020) - Fensome, Andrew; Ambler, Catherine M.; Arnold, Eric; Banker, Mary Ellen; Clark, James D.; Dowty, Martin E.; Efremov, Ivan V.; Flick, Andrew; Gerstenberger, Brian S.; Gifford, Roger S.; Gopalsamy, Ariamala; Hegen, Martin; et al.
Graphical abstract: Abstract: Herein, we disclose a new series of TYK2/ JAK1 inhibitors based upon a 3.1.0 azabicyclic substituted pyrimidine scaffold. We illustrate the use of structure-based drug design for the initial design and subsequent optimization of this series of compounds. One advanced example 19 met program objectives for potency, selectivity and ADME, and demonstrated oral activity in the adjuvant-induced arthritis rat model.